Avaliação das práticas de gestão ambiental dos empreendimentos flutuantes de turismo e lazer no baixo curso da bacia hidrográfica do rio Tarumã-Açu/AM - Iwata, Maria Jacqueline Ramos (My University, 2024)
The lower course of the Tarumã-Açu River, located in the western part of Manaus, is an area of significant tourist and environmental relevance. This area has been explored by a growing number of floating enterprises focused on leisure and tourism. These floating establishments, which include restaurants, bars and daily rentals for groups on weekends, contribute to the region's economy, being a popular destination for both local residents and tourists looking for a unique experience and in direct contact with nature. In order for this activity not to alter the local ecosystem, it is necessary to adopt sustainable practices aiming at the least possible impact on this natural area. In this sense, the objective of this work was to identify the main environmental management practices adopted in the floating leisure and tourism establishments located in the lower course of the Tarumã-Açu river basin, in the western part of the capital of Amazonas. To achieve the proposed objective, a qualitative research of an exploratory and descriptive nature was worked on, with 07 floating establishments that occurred in the months of April, May and June 2023; February and July 2024, the collection instrument used was the questionnaire and direct observation. The results indicated that the sampled floaters adopt the Sewage Treatment Plant (ETE) as a basic environmental management standard. In addition, other actions were identified, such as participation in lectures on environmental protection (71%); adoption of an environmental management program similar to the 5Rs of sustainability (57%); having a team responsible for managing solid waste (86%); having a team that manages sanitary effluents (57%). Environmental licensing has been a specific criterion adopted by all of this sample and 57% have a license granted by the Amazonas Environmental Protection Institute (IPAAM) and 43% have a licensing request in progress, however, IPAAM has granted them the authorization to collect and release effluents. A significant portion of the sample actively participates in the development of riverside communities, including low-income people in the workforce, in addition to valuing local commerce and participation in environmental actions, contributing to achieving the targets of SDGs 8.9; 12.b and 14.7 of the 2030 Agenda. Among the limitations that affected the research, the small sample size stands out, since most of the floating managers did not agree to participate in the study. The justification for this situation is related to judicial restrictions imposed by the Specialized Environmental Court - VEMA against the floating operators, followed by the drought in the summer of 2023, which completel paralyzed their activities. It is suggested that reflections be implemented that contemplate the responsibility and socio-environmental commitment not only of the managers of the leisure and tourism floating operators, but also of other agents, such as employees, tourists, visitors and communities surrounding Tarumã-Açu. And as a product of this study, the main results will serve as a starting point for future academic investigations that may expand the theme and continue with new reflections and critical awareness. [resumo fornecido pelo autor]
O baixo curso do rio Tarumã-Açu, localizado na zona oeste de Manaus, compõe uma área de significativa relevância turística e ambiental. Essa área tem sido explorada por uma crescente quantidade de empreendimentos flutuantes voltados ao lazer e ao turismo. Esses flutuantes, que abrangem restaurantes, bares e locação de diárias para grupos nos fins de semana, contribuem para a economia da região, sendo um destino popular tanto para moradores locais quanto para turistas em busca de uma experiência diferenciada e em contato direto com a natureza. Para que essa atividade não altere o ecossistema local, é necessário a adoção de práticas sustentáveis visando o menor impacto possível sobre essa área natural. Neste sentido, o objetivo deste trabalho foi identificar as principais práticas de gestão ambiental adotadas nos flutuantes de lazer e turismo localizados no baixo curso da bacia hidrográfica do Tarumã-Açu, na zona oeste da capital amazonense. Para atingir o objetivo proposto, foi trabalhado com uma pesquisa qualitativa de caráter exploratório e descritivo, com 07 flutuantes que ocorreram nos meses de abril, maio e junho de 2023; fevereiro e julho de 2024, o instrumento de coleta utilizado foi o questionário e a observação direta. Os resultados indicaram que os flutuantes da amostra adotam como padrão básico de gestão ambiental a Estação de Tratamento de Esgoto - ETE. Além disso, foram identificadas outras ações, como a participação em palestras sobre a proteção do meio ambiente (71%); a adoção a algum programa de gestão ambiental similar ao 5Rs da sustentabilidade (57%); possui equipe responsável pelo gerenciamento dos resíduos sólidos (86%); possui equipe que gerencia os efluentes sanitários (57%). O licenciamento ambiental tem sido critério específico adotado por todos desta amostra e 57% tem o licenciamento concedido pelo Instituto de Proteção Ambiental do Amazonas- IPAAM e 43% estão com o pedido de licenciamento em andamento, porém, o IPAAM concedeu-lhes a outorga para captação e lançamento de efluentes. Uma parcela significativa da amostra tem participação ativa no desenvolvimento das comunidades ribeirinhas, incluindo na mão de obra pessoas de baixa renda, além de valorizarem o comércio local e a participação em ações ambientais, contribuindo para atingir as metas dos ODS 8.9; 12.b e 14.7 da Agenda 2030. Entre as limitações que afetaram a pesquisa, destaca-se a amostra reduzida, uma vez que a maior parte dos gestores dos flutuantes não aceitaram participar do estudo. A justificativa para tal situação está relacionada a restrições judiciais impostas pela Vara Especializada do Meio Ambiente - VEMA contra os flutuantes, seguida da estiagem do verão de 2023, que paralisou integralmente suas atividades. Sugere-se a implementação de reflexões que contemplem a responsabilidade e o compromisso socioambiental não somente dos gestores dos flutuantes de lazer e turismo, mas também de outros agentes, como os colaboradores, turistas, visitantes e comunidades do entorno do Tarumã-Açu. E como produto deste estudo, os principais resultados servirão de ponto de partida para futuras investigações acadêmicas que poderão ampliar o tema e dar continuidade com novas reflexões e consciência crítica. [resumo fornecido pelo autor]
Keywords: Turismo - Manaus (AM) - Aspectos ambientais; Gestão ambiental.; Lazer; Turismo sustentável; Tourism - Manaus (Brazil) - Environmental aspects; Environmental management; Leisure; Sustainable tourism